As concepções geográficas e pedagógicas que fundamentam a formação dos professores dos cursos de licenciatura em Geografia da Universidade Estadual do Oeste do Paraná (Unioeste) - Sinhoratti, Fabiana (2024)
This thesis investigates the theoretical and pedagogical conceptions that guide the training and teaching practices of graduates from the Geography Licensure courses at the State University of Western Paraná (Unioeste), in the Francisco Beltrão and Marechal Cândido Rondon campuses. Based on studies conducted by educational researchers, we highlight the importance of theoretical and methodological reflection in the teacher training process. The historical analysis reveals that geographical science in Brazil was initially influenced by European currents and later shaped by theoretical disputes during the military dictatorship, culminating in the development of Critical Geography. However, neoliberal policies implemented in the country, particularly from the 1990s onward, negatively impacted education and hindered advancements in teacher training. Conversely, this period also witnessed the intensification of a social movement in the western and southwestern regions of Paraná advocating for the state regulation of higher education. Until then, the region was primarily served by small institutions, including some municipal colleges. By the late 1990s and early 2000s, this struggle for state regulation finally succeeded with the establishment of Unioeste, which became a significant institution for the local society, contributing to the training of new professionals, particularly future geography teachers. This research points to gaps and challenges in aligning the Political-Pedagogical Projects (PPP) with essential educational conceptions relevant to the training process of geography teachers. Furthermore, through interviews with faculty members from geography licensure courses and teachers working in Basic Education who graduated from Unioeste, it was found that, despite theoretical advances in teacher training, a gap persists between critical pedagogical conceptions and their effective implementation in Basic Education. Although the Geography courses at Unioeste aim to prepare professionals capable of interpreting the world and its multiple dimensions within a critical framework, it was observed that most graduates from these courses—who are currently working in the Paraná state education system—demonstrated limited knowledge regarding the geographical and pedagogical conceptions investigated in this thesis.